Sugary Snack Consumption and Tooth Retention among Middle-aged Thai Adults - Naorungroj, Supawadee (J Int Soc Prev Community Dent, 2020)
OBJECTIVES: This study investigated whether the habit of consuming sugary snacks was independently associated with the loss of permanent teeth. MATERIALS AND METHODS: Eight hundred ninety-seven adults aged 35–65 from four communities in the lower regions of Southern Thailand completed a structured questionnaire interview and dental examinations. The independent variable was frequency of sweet snack consumption between meals in the previous week and coded as: never (0 days), occasionally (1–4 days), or frequently (≥5 days). The outcome was the number of permanent teeth (1–19 vs. ≥20 teeth). Multivariate logistic regression was used to examine the adjusted associations between sugary snack consumption and the number of retained teeth. Odds ratio (OR) and 95% confidence intervals (CI) were calculated. RESULTS: Approximately 23% of participants retained fewer than 20 permanent teeth. Approximately 30% of participants reported sugary snack intake most days. Fewer teeth were positively associated with high-frequency sugary snack consumption, older age, Muslim, ≤ 6 years of education, universal healthcare, infrequent tooth brushing, smoking, and alcohol consumption, but not sugar-sweetened beverages. After adjusting for sociodemographic characteristics and other potential confounders, the odds of having fewer teeth were higher among participants who frequently consumed sugary snacks (OR = 2.03, 95% CI = 1.21–3.39), but was not significantly different from those who occasionally consumed sugary snacks (OR = 0.93; 95% CI = 0.58–1.50) compared to nonsugary snack consumers. CONCLUSION: In this study, habitual sugary snack intake was associated with fewer teeth among middle-aged Thai adults. To improve oral health and prevent further tooth loss, efforts to reduce sugary snack consumption would be needed.